Inhibitory Monoclonal Antibodies against Mouse Proteases Raised in Gene-Deficient Mice Block Proteolytic Functions in vivo - Lund, Ida K.; Rasch, Morten G.; Ingvarsen, Signe; Pass, Jesper; Madsen, Daniel H.; Engelholm, Lars H.; Behrendt, Niels; Høyer-Hansen, Gunilla (Frontiers in Pharmacology, 2012)
Identification of targets for cancer therapy requires the understanding of the in vivo roles of proteins, which can be derived from studies using gene-targeted mice. An alternative strategy is the administration of inhibitory monoclonal antibodies (mAbs), causing acute disruption of the target protein function(s). This approach has the advantage of being a model for therapeutic targeting. mAbs for use in mouse models can be obtained through immunization of gene-deficient mice with the autologous protein. Such mAbs react with both species-specific epitopes and epitopes conserved between species. mAbs against proteins involved in extracellular proteolysis, including plasminogen activators (uPA, tPA), their inhibitor PAI-1, the uPA receptor (uPAR), two matrix metalloproteinases (MMP9 and MMP14), as well as the collagen internalization receptor uPARAP, have been developed. The inhibitory mAbs against uPA and uPAR block plasminogen activation and thereby hepatic fibrinolysis in vivo. Wound healing, another plasmin-dependent process, is delayed by an inhibitory mAb against uPA in the adult mouse. Thromboembolism can be inhibited by anti-PAI-1 mAbs in vivo. In conclusion, function-blocking mAbs are well-suited for targeted therapy in mouse models of different diseases, including cancer.